The Effect of Financial Literacy on Risk Tolerance as an Intervening Variable Against Decision Making - Rosnani Said; Sulhan Manaf; Sumarsih Sumarsih (SIMAK, 2023)
This study aims to analyze the effect of financial literacy and risk tolerance as an intervening variable on decision making. The phenomenon in this study is how financial literacy influences risk tolerance as an intervening variable on decision making (a Makassar Investor study during the Covid-19 pandemic). This research was conducted during the Covid-19 Pandemic, starting at the end of 2019 until the end of 2020, so that phenomena related to financial literacy, risk tolerance, and decision making for investors in Makassar had not existed before. This research used the Structural Equation Model (SEM) method with the Smart PLS 3.0 software program, the data source is primary data from 290 investors registered with securities companies in Makassar. Data were obtained through interviews and distributing questionnaires to determine the effect of financial literacy through investment risk tolerance on decision making. The results showed that the financial literacy factor through risk tolerance had no effect on financial decisions.